How Do Enterprises Benefit from Grid Connection? : The Case of Rural Electrification in Bangladesh - Samad, Hussain; Portale, Elisa (World Bank, Washington, DC, 2019)
Many of the enterprises that make up Bangladesh’s dominant nonfarm sector (85 percent of GDP) are located in rural areas (World Bank 2015). Electrifying them can be a major driving force behind economic growth. This study is a product of the Status of Energy Access Report (SEAR), an initiative of the Energy Sector Management Assistance Program at the World Bank.